It takes a network to defeat a network: What Collective Action practitioners can learn from research into corrupt networks - Camargo, Claudia Baez; Costa, Jacopo; Hans, Vanessa; Koechlin, Lucy; Wannenwetsch, Scarlet (Basel Institute on Governance, 2021)
This Policy Brief distils recommendations for Collective Action practitioners based on empirical insights on certain forms of corruption involving private-sector actors. Field research carried out in Tanzania and Uganda produced detailed case studies that show how informal networks link private and public sector actors to pursue common illicit goals (Baez Camargo et al, 2021), such as gaining an unfair business advantage, avoiding a sanction, decreasing taxes owed or jumping the queue at the point of delivery of public services. Corruption, most often bribery, is the currency that works to cement and nurture those networks. This Policy Brief is based on that research and a series of in-depth interviews with Collective Action practitioners working in Africa, Eastern Europe and Latin America.